Prediksi Lahan Terbangun di Wilayah Peri-Urban Kota Bandung - Pramudya Alif; Ira Safitri Darwin (UNISBA Press, 2022)
Abstract. The rapid growth of Bandung City as the center of West Java Province and the center of the Bandung Metropolitan Area (BMA) has caused the development of the city to spread to peri-urban areas. Peri-urban areas affected by the spread of Bandung City include Cileunyi District, Rancaekek District, Jatinangor District which is located in the eastern part of Bandung City. As a result, the development of built-up land in the three sub-districts increased rapidly. This study aims to predict the development of built-up land in peri-urban areas in 2036 due to the spread of Bandung City. The methods used in this study are supervised image classification and Cellular Automata Markov. Analysis was carried out with ArcGis and TerrSet software. Digital elevation model, slope, population density, distance to road, distance to city center, and distance to industry are the driving variables used in this study to obtain land cover in 2036. The results of the study show that the kappa validation is 0.89. The accuracy value is in the very good category and is suitable to be used to predict land cover in 2036. Prediction of built-up land in the study area in 2036 reaches 5,104.75 Ha. The largest built-up areas are located in Cileunyi, Rancaekek, Jatinangor sub-districts with an area of ​​1,922.41 ha, 1,720.28 ha, and 1,456.87 ha, respectively. The development of built-up land leads to the west or approaches the city of Bandung. Abstrak. Pesatnya pertumbuhan Kota Bandung sebagai pusat Provinsi Jawa Barat dan pusat Bandung Metropolitan Area (BMA) menyebabkan perkembangan kota merembet ke wilayah peri-urban. Wilayah peri-urban yang terkena dampak perembetan Kota Bandung diantaranya Kecamatan Cileunyi, Kecamatan Rancaekek, Kecamatan Jatinangor yang terletak di bagian Timur Kota Bandung. Akibatnya perkembangan lahan terbangun di ketiga kecamatan meningkat dengan pesat. Studi ini bertujuan memprediksi perkembangan lahan terbangun di wilayah peri-urban pada tahun 2036 akibat perembetan Kota Bandung. Metode yang digunakan dalam studi ini adalah klasifikasi citra supervised dan Cellular Automata Markov. Analisis dilakukan dengan perangkat lunak ArcGis dan TerrSet. Digital elevation model, kemiringan lereng, kepadatan penduduk, jarak terhadap jalan, jarak terhadap pusat kota, dan jarak terhadap industri merupakan variabel pendorong yang digunakan dalam studi ini untuk memperoleh tutupan lahan tahun 2036. Hasil studi menunjukkan validasi kappa adalah 0,89. Nilai akurasi termasuk kategori sangat baik dan layak digunakan untuk memprediksi tutupan lahan tahun 2036. Prediksi lahan terbangun di wilayah studi tahun 2036 mencapai 5.104,75 Ha. Lahan terbangun terbesar secara berurutan berada di Kecamatan Cileunyi, Rancaekek, Jatinangor dengan luas masing-masing 1.922,41 Ha, 1.720,28 Ha, dan 1.456,87 Ha. Perkembangan lahan terbangun mengarah ke arah barat atau mendekati Kota Bandung.